PENERAPAN UI/UX PADA E-COMMERCE BATIK JAMBI DUO SERANGKAI BERBASIS WEB (STUDI KASUS GERAI BATIK JAMBI DUO SERANGKAI) - Kurniawan, Akhmad Yudiyanto; Sany, Ezrifal; Megawaty, Merti (Jurnal Manajamen Informatika Jayakarta, 2024)
User experience is a science that studies how to design and change a user's feelings, perceptions and behavior towards a display, service and performance of a product, system or service. User experience (UX) assesses how satisfied and comfortable a person is with a product, system and service. The user interface is one of the factors that determines the increase in traffic on a website. Because users interact with programming logic through the user interface. And the design of the user interface itself is very important considering that the more effective and efficient a design is, the more comfortable the user will be to linger on the website. The user interface is one of the most important factors in building a website. E-commerce is a dynamic set of application technologies and business processes that connect companies, consumers and certain communities through electronic transactions and trading of goods, services and information that is carried out electronically. The UI/UX on the Batik Duo Serangkai Jambi e-commerce website is to provide a solution to enhance the transparent postage feature, display popular products, increase information about product color and size, and create a visual experience that spoils the eyes for customers.